Narrative technique in Sherko Bekas's book (Kursi). - فەرەیدون قادر, ئاوارە (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
Narration is an artistic and literary device employed by the author in their text as a means to reach the intended meaning. In all the fields, narration is the basis for dialogues, events and descriptions. Therefore, it is a crucial process of content production. In order to deliver its message, narration depends on condition of the ages. Generally, narration plays an important role in all the literary genres, and it undergoes changes based on environment, time, place, conditions, history and society. It asserts its hegemony and establishes its position in the literary genres. The poet uses the technique of narration in his poem collection of Kursi with the aim of presenting some important agenda of narration. The main purpose is to connect the reader to time with the aim of comprehending the conditions and events while resorting to different ages, with regards to the sequence of time, history or ages.